GROUNDWATER LEVEL OBSERVATIONS AT THE PETROPAVLOVSK TEST SITE, KAMCHATKA - Kopylova G.N.; Lyubushin A.A.Jr.; Malugin V.A.; Smirnov A.A.; Taranova L.N. (My University, 2001)
An automatic system for groundwater level observations is described along with synchronous recordings of changes in groundwater level in wells and of atmospheric pressure made in 1996-1998 at two wells of the Petropavlovsk Test Site, Kamchatka. Attention is focused on coseismic and postseismic water level changes in relation to the December 5, 1997, magnitude 7.7 earthquake recorded at distances of 360-370 km from the wells. Cross-spectral analysis of water-level variations and atmospheric pressure changes together with information on earthquake-related water level behavior were used to estimate individual sensitivities of the wells to rapid changes in the stress and strain of water-saturated rocks.